What is the best biological parameter to predict erectile dysfunction in men aged >55 years with type 2 diabetes?. Issue 1 (8th July 2019) - Raharinavalona, Sitraka A; Chevalier, Nicolas; Gruel, Claude; N'toutoum, André‐Christian; Vélayoudom Céphise, Fritz‐Line
Abstract: To date, there is no evidence regarding the best biological marker to predict erectile dysfunction (ED) in men aged >55 years with type 2 diabetes. This prospective study included data from men aged >55 years with type 2 diabetes. ED was assessed by the International Index of Erectile Function 15‐item survey. Total testosterone (TT) levels and bioavailable testosterone were measured; the free testosterone index was calculated. Data from 155 men (aged 64 ± 7 years) were explored. The prevalence of ED and testosterone deficiency was 78.7% and 34.8%, respectively. After univariate analysis, TT and bioavailable testosterone were associated with ED ( P = 0.01). After multivariate analysis, and adjustment for age, body mass index, tobacco, alcohol, duration of diabetes, TT, bioavailable testosterone, vitamin D and high‐sensitivity C‐reactive protein, we found that only high‐sensitivity C‐reactive protein was significantly predictive of ED. TT could predict ED, but it lacks specificity. We found a potential role of high‐sensitivity C‐reactive protein as a predictive marker of ED in this targeted population. Abstract : Men with ED had lower levels of total testosterone and bioavailable testosterone compared to men without ED but the free testosterone index was not different. Surprisingly, the hsCRP was higher in men with ED compared to the others. The multivariate analysis found a new potential role of hsCRP as a predictive marker of ED in men with diabetes, aged >55 years.